Technical Institutions-Industry Interaction-Some New Dimensions and Realities - Patankar, P. R. (Journal of Engineering Education Transformations, 1997)
This subject has been under discussion on various forums for a long time in the past. The discussions were in most cases initiated by technical institutions and although both sides agreed in principle that such interaction is the need of the day, very little has actually come out in practice except at local and individual levels.